Deposition and characterisation of a diamond/Ti/diamond multilayer structure - Mallik, Awadesh Kumar (2024)
In this work, a diamond/Ti/diamond multilayer structure has been fabricated by successively following thin-film CVD and PVD routes. It has been found that a combined pre-treatment of the silicon base substrate, via argon plasma etching for creating surface roughness and, thereafter, detonation nanodiamond (DND) seeding, helps in the nucleation and growth of well-adherent CVD diamond films with a well-defined Raman signal at 1332 cm−1, showing the crystalline nature of the film. Ti sputtering on such a CVD-grown diamond surface leads to an imprinted bead-like microstructure of the titanium film, generated from the underlying diamond layer. The cross-sectional thickness of the titanium layer can be found to vary by as much as 0.5 µm across the length of the surface, which was caused by a subsequent hydrogen plasma etching process step of the composite film conducted after Ti sputtering. The hydrogen plasma etching of the Ti–diamond composite film was found to be essential for smoothening the uneven as-grown texture of the films, which was developed due to the unequal growth of the microcrystalline diamond columns. Such hydrogen plasma surface treatment helped further the nucleation and growth of a nanocrystalline diamond film as the top layer, which was deposited following a similar CVD route to that used in depositing the bottom diamond layer, albeit with different process parameters. For the latter, a hydrogen gas diluted with PH3 precursor recipe produced smaller nanocrystalline diamond crystals for the top layer. The titanium layer in between the two diamond layers possesses a very-fine-grained microstructure. Transmission electron microscopy (TEM) results show evidence of intermixing between the titanium and diamond layers at their respective interfaces. The thin films in the composite multilayer follow the contour of the plasma-etched silicon substrate and are thus useful in producing continuous protective coatings on 3D objects—a requirement for many engineering applications.